A Global Overview of the Impact of Peritoneal Dialysis First or Favored Policies: An Opinion. Issue 4 (July 2015) - Liu, Frank Xiaoqing; Gao, Xin; Inglese, Gary; Chuengsaman, Piyatida; Pecoits-Filho, Roberto; Yu, Alex
Given the ever-increasing burden of end-stage renal disease (ESRD) in a global milieu of limited financial and health resources, interested parties continue to search for ways to optimize dialysis access. Government and payer initiatives to increase access to renal replacement therapies (RRTs), particularly peritoneal dialysis (PD) and hemodialysis (HD), may have meaningful impacts from clinical and health-economic perspectives; and despite similar clinical and humanistic outcomes between the two dialysis modalities, PD may be the more convenient and resource-conscious option. This review assessed country-specific PD-First/Favored policies and their associated background, implementation, and outcomes. It was found that barriers to policy-implementation are broadly associated with government policy, economics, provider or healthcare professional education, modality-related factors, and patient-related factors. Notably, the success of a given country's PD-Favored policy was inversely associated with the extent of HD infrastructure. It is hoped that this review will provide a foundation across countries to share lessons learned during the development and implementation of PD-First/Favored policies.